A CASE STUDY OF AN AMERICAN LECTURER TEACHING SPEAKING TO THE SECOND-YEAR FAST-TRACK CLASSES AT ULIS, VNU(From a perspective of intercultural communication) = Điển cứu về một giáo viên người Mỹ dạy kĩ năng nói cho sinh viên chất lượng cao năm thứ hai tại trường đại học Ngoại ngữ, Đại học Quốc gia Hà Nội - Vũ, Thị Thu Lý (2020)
As one of the first attempts to raise an awareness of Intercultural communication, the paper aims at investigating the cultural problems, cultural adaptation of a visiting American lecturer who is teaching English in Vietnam as well as the attitudes of the students towards her behaviors. To fulfill this primary aim, qualitative method with two research instruments including interviews and observations were adopted. The participants of the study were an American lecturer and 41 second-year students of Fast-Track Program. The most significant finding of the research was that in spite of short-term living in Vietnam with a lot of culture shocks, the visiting American lecturer was successful to adapt Vietnamese culture and demonstrated high teacher credibility thanks to her strategies and the globalization going on in Vietnam. The paper, therefore, would serve as a good reference for both English language teachers and foreign language specialized students who desire to have a closer look at this issue or to improve their Intercultural sense.